Relative impact of different ERP forms on global manufacturing organizations: an exploratory analysis of a global manufacturing survey - Olson, David L.; Chae, Bongsug K.; Sheu, Chwen (My University, 2013)
There are many types of enterprise resource planning (ERP) systems, ranging from very large and very functional vendor products such as provided by SAP and Oracle, through in-house systems, and smaller vendor products. Thus there is a substantial range of enterprise computing support available for manufacturing organizations and their manufacturing planning and control. The Global Manufacturing Research Group (GMRG) has collected a systematic survey of manufacturing organizations around the world, providing a picture of manufacturing operations. We have taken GMRG data and organized it around seven levels of ERP functionality, and analyzed this data in terms of effectiveness in terms of how ERP systems are used in global manufacturing firms, their role in accomplishing manufacturing planning and control, the relationship between ERP forms and data management practices, the satisfaction firms have across ERP forms, and finally relative perceived benefits and costs across ERP forms.
Keywords: Enterprise resource planning systems; Global manufacturing organisations and practices; Manufacturing production and control; GMRG data; Supply chains; Impact of ERP